Tourism and hospitality management (Faculty of Tourism and Hospitality Management, WIFI Institut for Economic Promotion, Alexandreion Technological Educational Institution, 2009)
Međunarodni, multidisciplinarni časopis, u kojem se objavljuju istraživanja iz područja turizma i hotelske industrije.